THE ROLE OF INFORMATION TECHNOLOGY IN CREATING SUSTAINABILITY VALUE FOR FINANCIAL INSTITUTIONS IN 2020 : a scenario planning approach - Toscano, Matheus (My University, 2011)
The growing importance of global sustainability issues has been causing many changes to the financial services industry. Facts such as climate change, social development and the financial crisis in 2008 have been making banks reconsider the manner that they consider environmental, social and economic factors in their decision-making process. At the same time, information technology (IT) has been transforming the financial service industry and its fast development has casted doubts on the way it should be managed within an organization. This current changing environment brings a number of uncertainties to the future that cannot be addressed using traditional forecasting techniques. This research investigates how IT can bring value to sustainability in the financial service industry in 2020. Through the use of a scenario planning technique, we analyzed how trends in the current environment (considering the relation between sustainability, financial institutions an IT) can lead to four different future scenarios. Then, we discussed how IT can improve a bank’s sustainability performance, considering the limitations of each scenario.